Twenty Years of Amos Research. (October 2019) - Carroll R., M. Daniel
This article is a selective survey of the last twenty years of Amos research, which has witnessed robust discussion in multiple directions. It groups these trends into five very broad areas: (1) the possibility of positing an eighth-century setting for the prophet and the historical reliability of the book, (2) work on the redaction of the book and potential connections to the history of the composition of the Book of the Twelve, (3) theological themes of particular contemporary interest, (4) recent insights into the translation techniques of LXX Amos, and (5) the reception of Amos across the centuries, with a special focus on the views of women and minority and global communities. There is a range of scholarly positions in several of these areas and new questions being asked, all of which portends continued vitality in Amos research in the foreseeable future.